Spatial adaptation of eosinophils and their emerging roles in homeostasis, infection and disease - Arnold, Isabelle C.; Munitz, Ariel (Nature reviews. Immunology, 2024)
Eosinophils are bone marrow-derived granulocytes that are traditionally associated with type 2 immune responses, such as those that occur during parasite infections and allergy. Emerging evidence demonstrates the remarkable functional plasticity of this elusive cell type and its pleiotropic functions in diverse settings. Eosinophils broadly contribute to tissue homeostasis, host defence and immune regulation, predominantly at mucosal sites. The scope of their activities primarily reflects the breadth of their portfolio of secreted mediators, which range from cytotoxic cationic proteins and reactive oxygen species to multiple cytokines, chemokines and lipid mediators. Here, we comprehensively review basic eosinophil biology that is directly related to their activities in homeostasis, protective immunity, regeneration and cancer. We examine how dysregulation of these functions contributes to the physiopathology of a broad range of inflammatory diseases. Furthermore, we discuss recent findings regarding the tissue compartmentalization and adaptation of eosinophils, shedding light on the factors that likely drive their functional diversification within tissues. This Review by Arnold and Munitz discusses the diverse roles of eosinophils in the settings of tissue homeostasis, infection, allergy and cancer. The authors explain the molecular mechanisms that enable eosinophils to adapt to diverse tissue types and conditions, and they consider the therapeutic potential of eosinophil-depleting drugs in the clinic.